Some Identities on the Twisted (ℎ,𝑞)-Genocchi Numbers and Polynomials Associated with 𝑞-Bernstein Polynomials - Seog-Hoon Rim; Sun-Jung Lee (International Journal of Mathematics and Mathematical Sciences)
We give some interesting identities on the twisted (ℎ,𝑞)-Genocchi numbers and polynomials associated with 𝑞-Bernstein polynomials.